IMPLEMENTASI PROGRAM PEMBINAAN ANAK TERLANTAR (Studi pada Dinas Sosial Kota Malang) - Nina Agustina; Dody Setyawan (Universitas Tribhuwana Tunggadewi, 2019)
Abstract: Children's rights are part of human rights in the 1945 Constitution. In Article 34 paragraph 1, it is stated that the poor and neglected children are cared for by the state. The phenomenon of homeless children is closely related to the protection of children's rights and not only national but also international. The purpose of this study was to find out the implementation of homeless children’s development programs in Malang along with its supporting and inhibiting factors. This study used a qualitative research method, with a snowball sampling and predetermined informants. The data collection technique was interviews, observation and documentation. And then the data analysis technique used data reduction, data display, and conclusion drawing/verification. And for the data validity it used technical triangulation. Results of the study that the implementation of homeless children development programs conducted by the Malang Social Service Agency was less effective, from a communication perspective, resources, disposition or attitude and bureaucratic structure. The supporting factors included a strong commitment from the implementers of homeless children development programs, a financial assistance from the Ministry of Social Affairs and a good cooperation between the provincial government and non-governmental organizations in organizing social welfare in Malang. While the inhibiting factors were the lack of shelter or shelter specifically for homeless children, lack of willingness from the orphanage to accommodate or provide shelter to the homeless children because of the negative impact that might occure and they did not have psychologists. Keywords: Homeless Children Development Program Abstrak: Hak asasi anak merupakan bagian dari hak asasi manusia yang termuat dalam Undang-Undang Dasar Negara 1945. Dalam pasal 34 ayat 1 disebutkan bahwa fakir miskin dan anak-anak terlantar dipelihara oleh negara. Fenomena tentang anak terlantar sangat erat kaitannya dengan perlindungan hak-hak anak dan tidak hanya bersifat nasional tetapi bersifat internasional. Tujuan penelitian ini adalah untuk mengetahui implementasi program pembinaan anak terlantardi Kota Malang beserta faktor pendukung dan penghambatnya. Penelitian ini menggunakan metode penelitian kualitatif, dengan sampel snowball sampling dengan informan yang telah ditentukan, teknik pengumpulan datayaitu wawancara, observasi dan dokumentasi. Teknik analisis data menggunakan data reduction (reduksi data), data display (penyajian data), dan conclusion drawing/verification (penarikan kesimpulan/verifikasi) serta keabsahan data dengan triangulasi teknik. Hasil penelitian bahwa Implementasi program pembinaan anak terlantar yang dilakukan oleh Dinas Sosial Kota Malang dapat dikatakan belum efektif, dari perspektif komunikasi, sumber daya, disposisi atau sikap dan struktur birokrasi. Faktor pendukung yang meliputi adanya kesungguhan komitmen yang kuat dari para pelaksana program pembinaan anak terlantar serta adanya bantuan dana dari kementrian sosial dan kerja sama yang baik antara, pemerintah provinsi dan lembaga swadaya masyarakat penyelenggara kesejahteraan sosial di Kota Malang. Sedangkan faktor penghambatnya belum memiliki shelter atau tempat penampungan khusus anak terlantar tersebut, kurangnya kesediaan dari panti asuhan untuk menampung atau membeikan tempat tinggal kepada anak terlantar karena dikhawatirkan dapat memberikan dampak negatif serta tidak dimilikinya tenaga ahli psikologi. Kata Kunci: Program Pembinaan Anak Terlantar